An annotated list of the type specimens of Tortricidae (Lepidoptera) in the collection of Zoological Institute, St. Petersburg, Russia. 1. Types of species described by O. Bremer, A. M. Djakonov, N. G. Erschoff, and A. M. Gerasimov - Nedoshivina, Svetlana V. (Zootaxa, 2015)
The primary types of 15 tortricid species described by O. Bremer, A. M. Djakonov, N. G. Erschoff, and A. M. Gerasimov deposited in the collection of Zoological Institute in St. Petersburg, Russia (ZISP) are listed and discussed. Lectotypes are designated for eight of these: Lazotaenia [sic.] aurichalcana Bremer, 1864; Ptycholoma plumbeolana Bremer, 1864; Tortrix euxina Djakonov, 1929; Diceratura rhodograpta Djakonov, 1929; Penthina enervana Erschoff, 1877; Tortrix (Idiographis) excentricana Erschoff, 1877; Conchylis nomadana Erschoff, 1874; Cochylis pistrinana Erschoff, 1877. Descriptions of the labels and photographs of adults are given for each species. Type specimens of two other species presumed to be deposited in ZISP, Bactra griseana Djakonov, 1929 and Lazotaenia [sic.] quinquemaculana Bremer, 1864, were not found in the collection and presumably are lost.